Study and post mortem analysis of steel ladle porous plug to improve bottom purging efficiency for cleaner steel. (July 2019) - Nag, Moumita; Agrawal, Tushar; Nag, Biswanath; Singh, Brijender; Biswas, Subir
Abstract: To achieve homogenous temperature and composition of steel by fostering of slag metal refining reaction Argon gas is purged through bottom purging blocks into the steel bath. Purging is the most important activitiy in secondary steel refining process. For smooth running of the process with less downtime, plug performance need to align with operation without failure. Metal penetration inside the segments of plug is one of the frequent phenomena observed that leads to partial or full choking. This may occur from both material & operational variabilities. During post mortem analysis of choked porous plugs several concerns came into the surface which act as constraints to achieve desired life of plug. Investigation reveals the thermal susceptibility of the different refractory components of plug under cyclic application guides the performance of device. Apart from material quality combination of right operational practises along with the proper maintenance regime determines further the destiny of the plug. This paper will describe about the different operational challenges faced by plugs and probable way out to improve the performance. Highlights: Study & Post mortem analysis. Steel Ladle Porous Plug Bottom purging. Secondary Refining Refractory